Minimizing communication cost for reconfigurable slot modules - Fekete, Sandor P.; Van Der Veen, Jan C.; Majer, Mateusz; Teich, Jürgen (Proceedings of 16th International Conference on Field Programmable Logic and Applications, 2006)
We discuss the problem of communication-aware module placement in array-like reconfigurable environments, such as the Erlangen Slot Machine (ESM). Bad placement of modules may degrade performance due to increased signal delays and wastes chip space for the reconfigurable multiple bus. We present integer linear programming (ILP) formulations that address both of these problems; both ILPs can be used stand-alone or as building blocks for more involved mathematical models. We validate our models by demonstrating their usefulness for a set of realistic benchmarks. © 2006 IEEE.
UnivIS-Import:2015-04-16:Pub.2006.tech.IMMD.inform.minimi